Determinants of Financial Performance of MSMEs in Indonesia Through Payment Gateway - Budi Gautama Siregar; Aswadi Lubis Aswadi (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to assess the impact of financial literacy and management on the financial performance of MSMEs from an Islamic perspective through the use of payment gateways in Indonesia. A total of 95 Muslim entrepreneurs engaged in micro, small and medium enterprises across Indonesia were sampled in this study. This study uses quantitative method with Structural Equation Model (SEM) approach as an analytical tool, and utilises Smart PLS software version 3.0 to support data analysis. The results of the analysis show that financial literacy and financial management are able to positively and significantly influence payment gateways and financial performance of MSME players in Indonesia, in accordance with the hypothesis proposed in this research. In addition, payment gateway variables can also positively and significantly influence the financial performance of MSMEs in Indonesia. By applying financial literacy and financial management in MSME transantion activities through payment gateways, it is expected to survive and  continue to improve the financial performance of MSMEs in Indonesia. The research findings are expected to contibute significantly to stakeholders who play a role in improving financial literacy and management in Indonesia. In addition, financial awareness among the MSME community is crucial, as is an understanding of fintech technologies such as payment gateways. Each individual needs to pay attention to this in order to manage funds wisely and optimally to achieve the expected results.